An overview of Malay traditional houses: the relationship of architectural components, cultural heritage and heritage preservation - Sulaiman, Norhafizatullakmar; Kamaruddin, Zumahiran (2013)
This paper presents an overview on identifying key components related to preservation practice of Malay traditional houses and its architectural components that is prevalent in different places of Peninsular Malaysia. The trends of the studies revealed that the preservation practice of Malay traditional houses is still not well exposed and presented in order. In the past decades, there are man researches on the Malay vernacular architecture especially on traditional houses. The overall review was derived from more than 50 studies of past researchers related to cultural heritage and heritage building preservation focusing on Malay traditional houses. The component of the traditional Malay houses comprises of the architectural elements and types of carved components. These include the aesthetical elements of wood carvings at the traditional houses which promote the uniqueness of the houses that is worth to be preserved. The reviews of the research conclude that there is no significant preservation guideline for Malay traditional houses that have been documented. The finding highlighted the relationship between architectural component, cultural heritage and heritage preservation and also the potential of Malay traditional houses in Peninsular of Malaysia.